Titanium alloy powder, titanium alloy and preparation method of titanium alloy

By using Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1~1.5)C spherical titanium alloy powder and combined with metal powder injection molding technology, the problem of difficulty in preparing high-strength titanium alloys in the existing process is solved, and a titanium alloy product with high strength and excellent mechanical properties is achieved.

CN119549699APending Publication Date: 2025-03-04GOERTEK INC +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311297939.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2023-10-08
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Currently, it is difficult to prepare high-strength titanium alloys in metal powder injection molding process.

Method used

Titanium alloy powder with nominal component Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1~1.5)C and microscopic morphology is spherical, and titanium alloy is prepared by metal powder injection molding technology. The process includes mixing the titanium alloy powder with a binder and granulating it, and after the first degreasing, the second degreasing, insulation after sintering, and cooling, finally obtaining the titanium alloy.

Benefits of technology

It realizes high strength, excellent density, tensile strength, yield strength and elongation, and supports mass production of small parts with complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549699A_ABST
    Figure CN119549699A_ABST
Patent Text Reader

Abstract

The invention discloses titanium alloy powder, titanium alloy and a preparation method of the titanium alloy, and belongs to the technical field of powder metallurgy materials. The nominal composition of the titanium alloy powder comprises Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1-1.5) C spherical powder, and the Ti-5Al-5Mo-5V-1Cr-1Fe The titanium alloy powder provided by the invention can be used for preparing the high-strength titanium alloy with excellent mechanical properties through a metal powder injection molding technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder metallurgy materials, and in particular to titanium alloy powder, titanium alloy and a preparation method thereof. Background Art

[0002] Titanium alloys have the advantages of low density, high specific strength, and corrosion resistance, and are widely used in aerospace, automobiles, consumer electronics, and other fields. In recent years, the demand for lightweight and high-strength titanium alloy materials has become increasingly strong.

[0003] Metal powder injection molding technology is a forming process that combines powder metallurgy technology with injection molding technology. It combines the advantages of low process cost and injection molding technology that can mass-produce parts with complex shapes. It is particularly suitable for mass production of small parts with complex structures.

[0004] However, it is difficult to prepare high-strength titanium alloys using the current metal powder injection molding process. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a titanium alloy powder, a titanium alloy and a preparation method thereof, aiming to solve the problem that the current metal powder injection molding process is difficult to prepare high-strength titanium alloy.

[0006] To achieve the above object, the present invention provides a titanium alloy powder, which includes Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1~1.5)C spherical powder.

[0007] Optionally, the particle size of the spherical powder is not greater than 25 μm.

[0008] Optionally, the oxygen content of the spherical powder is not higher than 1600 ppm.

[0009] To achieve the above object, the present invention provides a titanium alloy, which is prepared by metal powder injection molding of the above titanium alloy powder.

[0010] To achieve the above-mentioned purpose, the present invention proposes a method for preparing the above-mentioned titanium alloy, comprising the following steps: mixing titanium alloy powder with a binder, granulating to obtain feed; adding the feed to an injection machine for injection injection to obtain an injection product; the injection product undergoes a first degreasing, a second degreasing, sintering, heat preservation, and cooling to obtain a titanium alloy.

[0011] Optionally, the adhesive comprises a wax-based adhesive, and the first degreasing comprises degreasing using a trichloroethylene solution.

[0012] Optionally, the binder comprises a plastic-based binder, and the first degreasing comprises degreasing using oxalic acid.

[0013] Optionally, the injection temperature includes four different injection temperatures; and / or, the injection temperature is 120°C to 180°C.

[0014] Optionally, the second degreasing includes heating the temperature to 300° C. to 550° C. and then performing heat preservation degreasing, and the duration of the heat preservation degreasing is not less than 3 hours.

[0015] Optionally, the temperature of the heat preservation after sintering is 1000° C. to 1300° C.; and / or the time of the heat preservation after sintering is 1 h to 5 h.

[0016] The beneficial effects of the present invention are as follows: the titanium alloy powder provided by the present invention increases the proportion of carbon element in the raw material metal powder for preparing TC18 titanium alloy, forming a titanium alloy powder with a nominal composition of Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1~1.5)C and a spherical micromorphology, which can support the preparation of high-strength titanium alloys. The titanium alloy powder provided by the present invention can support the metal powder injection molding process to prepare titanium alloy finished products with excellent density, tensile strength, yield strength and elongation. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 This is a scanning electron microscope image of the Ti-5Al-5Mo-5V-1Cr-1Fe-0.5C spherical powder used in Example 1 of the present invention.

[0019] Figure 2 This is a scanning electron microscope metallographic photograph of the sample used for the tensile test in Example 1 of the present invention when it was sintered at 1300° C. for 1 hour.

[0020] Figure 3 This is a photograph of the tensile sample of Example 1 and Example 2 of the present invention after sintering at 1300°C for 1 hour.

[0021] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0023] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter pertains.

[0024] Titanium alloys have the advantages of low density, high specific strength, and corrosion resistance, and are widely used in aerospace, automobiles, consumer electronics, and other fields. In recent years, the demand for lightweight and high-strength titanium alloy materials has become increasingly strong.

[0025] Metal powder injection molding technology is a forming process that combines powder metallurgy technology with injection molding technology. It combines the advantages of low process cost and injection molding technology that can mass-produce parts with complex shapes. It is particularly suitable for mass production of small parts with complex structures.

[0026] However, it is difficult to prepare high-strength titanium alloys using the current metal powder injection molding process.

[0027] In order to solve the above problems, the present invention provides a titanium alloy powder, wherein the nominal composition of the titanium alloy powder includes Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1-1.5)C spherical powder.

[0028] The nominal composition of titanium alloy materials has a conventional compilation rule. In GB / TT3620.1 "Titanium and Titanium Alloy Grades and Chemical Composition", the nominal chemical composition of titanium alloy grades only lists the elements that must be controlled. The determination of the element content in the nominal chemical composition should be based on the arithmetic mean of its control range. For example, in the GB / TT3620.1 standard, the nominal composition of the existing TC18 titanium alloy is Ti-5Al-5Mo-5V-1Cr-1Fe. In fact, the mass fraction of Al is allowed to be in the range of 4.4% to 5.7%, the mass fraction of Mo is in the range of 4.0% to 5.5%, the mass fraction of V is in the range of 4.0% to 5.5%, and the mass fraction of Cr is in the range of 0.5% to 1.5%. C is regarded as an impurity that affects the structure of α-β titanium alloys, so the C content is required to be less than 0.08% by mass. Accordingly, the carbon content of the titanium alloy powder used to prepare TC18 titanium alloy is less than 0.08%.

[0029] In this scheme, any value in the range of (0.1~1.5)C has the same meaning as the values ​​in "5Al", "5Mo", "5V", "1Cr" and "1Fe", and they are all the arithmetic mean of the element addition control range. This scheme increases the proportion of carbon element in the raw metal powder for preparing TC18 titanium alloy, and uses the industrially mature atomized metal powder preparation method to make the molten metal flow rapidly impact, separate and condense into tiny particles by using high-speed and high-pressure airflow, high-speed rotating centrifugal force or other mechanical methods to form a titanium alloy powder with a nominal composition of Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1~1.5)C and a spherical micromorphology, which can support the preparation of high-strength metal powder injection molding titanium alloy.

[0030] In some embodiments, the titanium alloy powder includes Ti-5Al-5Mo-5V-1Cr-1Fe-0.2C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.3C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.4C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.5C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.6C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.7C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.8C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.9C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.10 0.7C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.8C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-0.9C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-1C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-1.1C spherical powder Ti-5Al-5Mo-5V-1Cr-1Fe-1.2C spherical powder, Ti-5Al-5Mo-5V-1Cr-1Fe-1.3C spherical powder or

[0031] Ti-5Al-5Mo-5V-1Cr-1Fe-1.4C spherical powder.

[0032] Furthermore, the particle size of the spherical powder is not greater than 25 μm. In this solution, the particle size of the spherical powder is not greater than 25 μm, which has the advantages of high density, low porosity, uniform particle size, good fluidity, etc., and can meet the preparation of fine titanium alloy products with complex shapes.

[0033] In some embodiments, the particle size of the spherical powder is 5 μm to 10 μm, 10 μm to 15 μm, 15 μm to 20 μm, or 20 μm to 25 μm.

[0034] Furthermore, the oxygen content of the spherical powder is not higher than 1600ppm. In this solution, trace oxygen can improve the hardness and strength of the titanium alloy, but when it exceeds 1600ppm, it will drastically reduce the plasticity, fracture toughness, cold formability and other properties of the titanium alloy.

[0035] In some embodiments, the spherical powder has an oxygen content of 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, or 1500 ppm.

[0036] To achieve the above purpose, the present invention proposes a titanium alloy, which is prepared by metal powder injection molding of the above titanium alloy powder. Metal powder injection molding technology (Metal Powder Injection Molding Technology, MIM) is a new type of powder metallurgy near-net shape molding technology formed by introducing plastic injection molding technology into the field of powder metallurgy. This process has the advantages of high precision, uniform structure, excellent performance, low production cost, etc., and can be used with the titanium alloy powder designed by the above scheme to prepare a titanium alloy with high strength, high density, strong toughness and excellent mechanical properties.

[0037] To achieve the above object, the present invention provides a method for preparing the above titanium alloy, comprising the following steps:

[0038] S1: mixing and granulating titanium alloy powder and a binder to obtain feed;

[0039] In this embodiment, the mixing includes mixing Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1-1.5)C spherical powder and a binder in a mixer according to a certain powder loading amount.

[0040] In some embodiments, the mixer is a V-type mixer.

[0041] In some embodiments, the loading amount is any value between 60% and 70%, such as 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68% or 69%. Preferably, the loading amount is between 63% and 68%.

[0042] In some embodiments, the mixing time is no less than 30 min.

[0043] In some embodiments, the mixed titanium alloy powder and binder are kneaded and crushed before granulation, and the kneading is performed using an SH-2 atmosphere kneader at a kneading temperature of 160-170°C for a kneading time of not less than 2 hours. Preferably, the kneading temperature is 165°C.

[0044] In some embodiments, the granulation equipment is a CF-Ф60 double-wrist extrusion granulator, the granulation temperature is 160-165°C, the extrusion speed is 10-45r / min, the feeding speed is 10-32r / min, and the cutting speed is 300-900r / min.

[0045] In some embodiments, the particle size of the feed material is 2 to 4 mm.

[0046] S2: adding the feed material to an injection machine and injecting it to obtain an injection product;

[0047] In some embodiments, the injection is performed using an EM120-SVP / 2 Zhenxiong 120-ton injection molding machine, and the injection temperature, injection pressure, injection speed, and holding time are set. The feed is injected into the stretch bar mold at a sol position of 45 mm, and the mold temperature is slightly higher than room temperature.

[0048] In some embodiments, the injection temperature is 140° C. to 160° C., the injection pressure is 93 bar to 96 bar, the injection speed is 117 mm / s to 123 mm / s, the holding time is 7.5 to 9 seconds, and the mold temperature is 40° C. to 50° C. By operating within the injection step parameter range of the above scheme, spraying and short shots can be avoided, thereby avoiding bubbles, weld lines or incomplete filling.

[0049] S3: The injection product is subjected to a first degreasing, a second degreasing, sintering, heat preservation, and cooling to obtain a titanium alloy;

[0050] In this scheme, the temperature is controlled during both the first and second degreasing. After two degreasing processes, the binder is gradually discharged along the tiny channels between the titanium alloy powder particles. After completely removing the binder for auxiliary injection, a degreased green body is obtained. The green body is then sintered, kept warm, and cooled, so that the porous green body shrinks to a densified titanium alloy with mechanical strength after degreasing. Sintering is usually a solid-phase diffusion method. When a titanium alloy is prepared by a mixed element method, the alloying elements in the titanium alloy will appear in a transient liquid phase or provide diffusion channels during sintering, promoting the densification process. In this scheme, no subsequent heat treatment is required after the titanium alloy is prepared. The process is simple, the cost is low, the application range is wide, and it can be mass-produced.

[0051] Furthermore, the binder includes a wax-based binder, and the first degreasing includes degreasing with a trichloroethylene solution. The wax-based binder has a low viscosity and is easy to volatilize, so it is easier to mix and is conducive to the uniform dispersion of various elements in the green body.

[0052] In some embodiments, the wax-based binder is a paraffin wax binder.

[0053] In some embodiments, the degreasing method using trichloroethylene solution is a solvent degreasing method, and the temperature range of the trichloroethylene solution is 38°C to 60°C.

[0054] In some embodiments, the first defatting includes keeping the injection product at 38° C. to 60° C. for 8 to 24 hours, and the keeping time is 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 22 hours.

[0055] Furthermore, the binder includes a plastic-based binder, and the first degreasing includes degreasing with oxalic acid. The plastic-based binder has high viscosity and low volatility, and needs to use a mixer with high shear force and adjust the temperature. The mixing conditions and injection conditions of the plastic-based binder are more complicated than those of the wax-based binder, and the degreasing difficulty is also greater than that of the wax-based binder. However, the plastic-based binder is not easy to deform after the second degreasing and heating in the subsequent process, so the deformation of the sintered part is relatively small after using the plastic-based binder.

[0056] In some embodiments, the plastic-based binder is a resin compound, such as POM (polyoxymethylene resin) and the like.

[0057] In some embodiments, the first degreasing includes placing the injection product in an oxalic acid degreasing furnace for acid catalytic degreasing, and the degreasing time is not less than 8 hours.

[0058] Further, the injection temperature includes four different injection temperatures; and / or, the injection temperature is 120°C to 180°C.

[0059] In some embodiments, the injection temperature includes a first-stage injection temperature, a second-stage injection temperature, a third-stage injection temperature, and a fourth-stage injection temperature. The first-stage injection temperature is used for the anti-saliva stage, and the temperature is relatively low compared to the second-stage injection temperature and the third-stage injection temperature, in order to prevent the feed from flowing out of the nozzle under the action of internal pressure, but the first-stage injection temperature is too low to increase the injection pressure. The second-stage injection temperature and the third-stage injection temperature are used for the heating zone, which is located in the middle part of the barrel of the injection instrument. Compared with the remaining temperature sections, the temperature is higher, in order to increase the fluidity of the feed. The fourth-stage injection temperature is used for the area near the hopper in the unloading area, and the temperature is relatively low compared to the first-stage injection temperature, the second-stage injection temperature, and the third-stage injection temperature. The fourth-stage injection temperature is to preheat the feed. If the temperature is too high, the screw is easy to slip and thus affect the feeding and conveying. If it is too low, the screw torque is large.

[0060] In some embodiments, the injection temperature includes a first stage injection temperature, a second stage injection temperature, a third stage injection temperature and a fourth stage injection temperature. The first stage injection temperature is 135°C to 165°C, the second stage injection temperature is 155°C to 180°C, the third stage injection temperature is 150°C to 175°C, and the fourth stage injection temperature is 115°C to 140°C.

[0061] Furthermore, the second degreasing includes heating to 300°C to 550°C and then heat-insulating for degreasing, and the duration of the heat-insulating degreasing is not less than 3 hours.

[0062] In some embodiments, the second debinding is performed using a BFZS1903111 molybdenum sheet high vacuum sintering furnace.

[0063] In some embodiments, the second degreasing is carried out by heating the temperature to the first heat preservation degreasing temperature at a constant heating rate and then keeping it warm for at least 1 hour, heating the temperature to the second heat preservation degreasing temperature and then keeping it warm for at least 1 hour, and heating the temperature to the third heat preservation degreasing temperature and then keeping it warm for at least 1 hour.

[0064] In some embodiments, the second degreasing process is heated at a rate of 5°C / min, and maintained at three different temperature sections of 300°C, 450°C, and 550°C for 1 hour each.

[0065] Furthermore, the temperature of the heat preservation after sintering is 1000° C. to 1300° C.; and / or the heat preservation time after sintering is 1 h to 5 h.

[0066] In some embodiments, the temperature is raised to the sintering temperature at a constant heating rate and then maintained at the temperature.

[0067] In some embodiments, the temperature is raised to 1000° C. to 1300° C. at a heating rate of 10° C. / min and then maintained at that temperature for 1 h to 5 h.

[0068] In some embodiments, the temperature of holding after sintering is 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C or 1290°C.

[0069] In some embodiments, the holding time after sintering is 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h or 4.5 h.

[0070] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0071] Embodiment 1:

[0072] 2 kg of Ti-5Al-5Mo-5V-1Cr-1Fe-0.5C spherical powder was premixed with a wax-based binder in a V-type mixer for 30 min, with a powder loading of 65%, a spherical powder particle size of 25 μm, and an oxygen content of 1600 ppm to obtain a mixed powder.

[0073] The mixed powder was put into an SH-2 atmosphere mixer for kneading. The kneading atmosphere was argon. The kneading temperature was 165° C. and the kneading time was 2 h to obtain a kneaded product.

[0074] The kneaded product was crushed and granulated in a CF-Ф60 double-arm extruder granulator. The granulation temperature was 165°C, the extrusion speed was 30r / min, the feeding speed was 20r / min, the cutting speed was 600r / min, and the cutting particle size was 3mm to obtain the feed.

[0075] The feed material was placed in the EM120-SVP / 2 Zhenxiong 120-ton injection machine for injection, and the injection mold was a stretch strip mold. The injection parameters were as follows: the first stage injection temperature was 140°C, the second stage injection temperature was 160°C, the third stage injection temperature was 155°C, the fourth stage injection temperature was 120°C, the injection pressure was 95 bar, the injection speed was 120 mm / s, the holding time was 8 s, the sol position was 45 mm, and the mold temperature was 45°C to obtain the injection product.

[0076] The injection product was degreased for the first time and placed in a 60°C trichloroethylene solution. After 8 hours, the first degreased product was obtained. The first degreased product was placed in a BFZS1903111 molybdenum sheet high vacuum sintering furnace for a second degreasing. The second degreasing was heated at 5°C / min, and the temperature was kept at 300°C, 450°C, and 550°C for 1h each. Then, the temperature was raised to 1000°C at 10°C / min and kept for 5h. Finally, it was cooled to room temperature to obtain a titanium alloy.

[0077] Embodiment 2:

[0078] The preparation method is the same as that of Example 1, except that:

[0079] The sintering temperature was raised to 1300°C at a rate of 10°C / min and kept at that temperature for 1 hour.

[0080] Embodiment 3:

[0081] The preparation method is the same as that of Example 2, except that:

[0082] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-0.2C spherical powder.

[0083] Embodiment 4:

[0084] The preparation method is the same as that of Example 2, except that:

[0085] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-0.4C spherical powder.

[0086] Embodiment 5:

[0087] The preparation method is the same as that of Example 2, except that:

[0088] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-0.8C spherical powder;

[0089] The adhesive is a plastic-based adhesive;

[0090] The injection parameters are as follows: the temperature of the first stage of injection is 165°C, the temperature of the second stage is 180°C, the temperature of the third stage is 175°C, and the temperature of the fourth stage is 140°C;

[0091] The first degreasing process is to put the injection product into an oxalic acid degreasing furnace for degreasing for 8 hours;

[0092] The holding time after sintering is 2h.

[0093] Embodiment 6:

[0094] The preparation method is the same as that of Example 2, except that:

[0095] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-1C spherical powder;

[0096] The adhesive is a plastic-based adhesive;

[0097] The first degreasing process is to put the injection product into an oxalic acid degreasing furnace for degreasing for 8 hours;

[0098] The holding time after sintering is 3h.

[0099] Embodiment 7:

[0100] The preparation method is the same as that of Example 2, except that:

[0101] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-1.2C spherical powder;

[0102] The holding temperature after sintering is 1200°C and the holding time is 3h.

[0103] Embodiment 8:

[0104] The preparation method is the same as that of Example 2, except that:

[0105] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-1.4C spherical powder;

[0106] The adhesive is a plastic-based adhesive;

[0107] The first degreasing process is to put the injection product into an oxalic acid degreasing furnace for degreasing for 8 hours;

[0108] The holding time after sintering is 3h.

[0109] Embodiment 9:

[0110] The preparation method is the same as that of Example 1, except that:

[0111] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-0.3C spherical powder;

[0112] The injection parameters are as follows: the temperature of the first injection stage is 145°C, the temperature of the second injection stage is 165°C, the temperature of the third injection stage is 160°C, and the temperature of the fourth injection stage is 125°C;

[0113] The holding time after sintering is 4h.

[0114] Embodiment 10:

[0115] The preparation method is the same as that of Example 1, except that:

[0116] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-0.7C spherical powder;

[0117] The injection parameters are as follows: the temperature of the first injection stage is 145°C, the temperature of the second injection stage is 165°C, the temperature of the third injection stage is 160°C, and the temperature of the fourth injection stage is 125°C;

[0118] The adhesive is a plastic-based adhesive;

[0119] The first degreasing process is to put the injection product into an oxalic acid degreasing furnace for degreasing for 8 hours;

[0120] The holding time after sintering is 4h.

[0121] Embodiment 11:

[0122] The preparation method is the same as that of Example 1, except that:

[0123] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-1.1C spherical powder;

[0124] The injection parameters are as follows: the temperature of the first injection stage is 150°C, the temperature of the second injection stage is 170°C, the temperature of the third injection stage is 165°C, and the temperature of the fourth injection stage is 130°C.

[0125] Comparative Example 1:

[0126] The preparation method is the same as that of Example 2, except that:

[0127] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-2C spherical powder;

[0128] Comparative Example 2:

[0129] The preparation method is the same as that of Example 2, except that:

[0130] The titanium alloy powder is Ti-5Al-5Mo-5V-1Cr-1Fe-2C spherical powder;

[0131] The sintering temperature was raised to 1350°C at a rate of 10°C / min and kept at that temperature for 1 hour.

[0132] Furthermore, the titanium alloys prepared in Examples 1-5 were subjected to density testing, mechanical property testing, and metallographic characterization.

[0133] Density test was carried out in accordance with GB / T1423-1996 national standard to obtain density test results; mechanical property test was carried out in accordance with GB / T228.1-2010 national standard, and mechanical property test included metal tensile test and metal stress test on sintered samples to obtain test results of tensile strength, elongation and yield strength; metallographic characterization samples were processed by the following method: polishing the samples with 800, 1500 and 3000 grit sandpaper, polishing with a polishing machine, and wiping and corroding the samples with Kroll reagent (hydrofluoric acid: concentrated nitric acid: water volume ratio of 1:3:15) for 50s. After corrosion, the samples were immediately placed in alcohol solution, left for 1min, and then dried with a hair dryer to obtain metallographic samples, which were then characterized with SU8100 cold field emission scanning electron microscope to obtain SEM images.

[0134] The test results are summarized in Table 1:

[0135] Table 1. Performance parameters of titanium alloy

[0136]

[0137] The carbon element introduced in Comparative Example 1 exceeds the limited range of the present invention, and its elongation is greatly affected, decreasing by 50% to 57%. The introduction of carbon elements will form TiC second phase strengthening particles during the sintering process of the spherical powder, improving the tensile strength and yield strength of the titanium alloy, but excessive carbon will destroy the α-β structural phase. The sintering temperature of Comparative Example 2 is relatively high, which will cause oxidation of the titanium alloy, seriously affecting the tensile strength, yield strength and elongation of the titanium alloy.

[0138] The injection molded high-strength titanium alloy prepared in Examples 1-5 of the present invention has a density greater than 98.0%, a room temperature tensile strength greater than 1200 MPa, a yield strength greater than 1100 MPa, and an elongation greater than 6.0%. The metal powder injection molded titanium alloy prepared in the present invention has excellent mechanical properties.

[0139] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A titanium alloy powder, characterized in that: The nominal composition of the titanium alloy powder includes Ti-5Al-5Mo-5V-1Cr-1Fe-(0.1-1.5)C spherical powder.

2. The titanium alloy powder according to claim 1, characterized in that The particle size of the spherical powder is no greater than 25 μm.

3. The titanium alloy powder according to claim 1, characterized in that The oxygen content of the spherical powder is not higher than 1600 ppm.

4. A titanium alloy, characterized in that: The titanium alloy powder is prepared by metal powder injection molding according to any one of claims 1 to 3.

5. A method for preparing a titanium alloy as claimed in claim 4, characterized in that: The following steps are involved: The titanium alloy powder is mixed with a binder and granulated to obtain a feed material; Adding the feed material into an injection machine and injecting it to obtain an injection product; The injection product undergoes first degreasing, second degreasing, heat preservation and cooling after sintering to obtain a titanium alloy.

6. The method for preparing a titanium alloy according to claim 5, characterized in that: The adhesive comprises a wax-based adhesive, and the first degreasing comprises degreasing using a trichloroethylene solution.

7. The method for preparing a titanium alloy according to claim 5, characterized in that: The binder includes a plastic-based binder, and the first degreasing includes degreasing using oxalic acid.

8. The method for preparing a titanium alloy according to claim 5, characterized in that: The injection temperature includes four different injection temperatures; And / or, the injection temperature is 120°C to 180°C.

9. The method for preparing a titanium alloy according to claim 5, characterized in that: The second degreasing includes heating to 300°C to 550°C and then maintaining the temperature for degreasing, and the duration of the degreasing is not less than 3 hours.

10. The method for preparing a titanium alloy according to claim 5, characterized in that: The temperature of the heat preservation after sintering is 1000° C. to 1300° C.; And / or, the heat preservation time after sintering is 1 hour to 5 hours.

Citation Information

Patent Citations

  • Titanium-base alloys

    CA838040A

  • Titanium base alloy

    CA861423A

  • Preparation method of titanium and titanium alloy spherical powder by vacuum induction melting gas atomization

    CN105127436A

  • Preparation method for TiC reinforced ultra-fine grain beta titanium and niobium based composite material

    CN107385250A

  • Nearly beta-type high-toughness titanium alloy and preparation method thereof

    CN109852845A